The Analysis of Factors Affecting Stock Prices in Cigarette and Toobaco Companies Listed on the Indonesia Stock Exchange - Kusmayadi, Kusmayadi; Dewi Sri Marsanti; Didiek Susilo Tamtomo; I Nyoman Romangsi; Sulistiyo, Sulistiyo (International Journal of Education, Vocational and Social Science, 2023)
This research has the aim to test the truth of Return On Equity (ROE), Earning Per Share (EPS), and Net Profit Margin (NPM) giving a simultaneous or partial effect on stock prices. In this research, the value of the company/company is proxied using Price to Book Value (PBV). This research uses a population of 5 Cigarette and Toobaco companies on the IDX list during the 2017-2021 period. Materials/data for the acquisition test are sourced from the financial report notes issued by the IDX. The sampling procedure uses a purposive sampling method that only uses Cigarette and Toobaco companies that are listed in succession during the 2017-2021 period, publishes historical stock prices during the research period, and does not experience losses during the research period. The number of samples that passed the category was 5 Cigarette and Toobaco companies which were studied for 5 years so the observation data were 25 observations. The results of the Coefficient of Determination in this study, which can be observed in Adjusted R Square, have a score of 42,9%. Stock prices can be influenced by ROE, EPS, and NPM, while the remaining 57,1% are influenced by other aspects that are not included in the study. Keywords : Earning per share, Return on Asset, Return on Equity, Net Profit margin, Stock Price